John Sidney Swan: a genuine article - Linzey, Kate (Architectural History Aotearoa, 2004)
The architect John Sidney Swan (1874-1936) represents a little represented group in the history of New Zealand architecture. At the establishment of the New Zealand Institute of Architects in 1905, Swan was one of few architects present, along with William Gray Young (1895-1962), who had been trained in New Zealand through the article system. While training "on the job" was a common occurrence in the early development of the building industry in this country, few of these architects achieved great renown. Swan however, was a prominent architect in his day, designing Erskine Chapel in Island Bay (1906), Saint Gerard’s Church in Mount Victoria (1908) and an unbuilt proposal for a Roman Catholic Basilica in Dufferin Street (1912). This renown may have been due to Swan’s mentor, Fredrick de Jersey Clere, the vocal English émigré architect. However, this mentorship does not wholly explain Swan’s prolific, and sometimes eccentric practice. This paper is part of an ongoing project to document Swan’s work, and develop an understanding of his particular style, which, on the one hand, reflects an awareness of the contemporary English fashions, and yet, on the other, rejoices in an almost theatrical excessiveness, quite contrary both to the evolving architectural austerity of modernism, and Clere’s more restrained style.